Tweacher: New proposal for Online Social Networks Impact in Secondary Education - Romero, Sebastián; Fardoun, Habib Moussa; Ruiz Penichet, Victor Manuel; Gallud, José Antonio (ADCAIJ: Advances in Distributed Computing and Artificial Intelligence Journal, 2013)
This paper presents and analyzes the potential uses and motivations of online social networks in education, with special emphasis on secondary education. First, we show several previous researches supporting the use of social networking as an educational tool and discuss Edmodo, an educative online social network. The work carried out during two academic years with senior students of primary and secondary schools is also analyzed. After that we present Tweacher an educative social network application and evaluate its use in the classroom to prove its useful use between teachers and students. This research has allowed us to see the reality of social network use among young people and identify the challenges of its application to education environment.